Survey on Awareness of Parthenium Infestation and its Ill effects in Andhra Pradesh, India - Neelima, T. L.; Reddy, M. D.; Madhavi, M. (International Journal of Bio-resource and Stress Management, 2010)
A survey on awareness of Parthenium infestation and its ill effects was conducted in 8 districts of Andhra Pradesh state in India by selecting 3 mandals (block) in each district, 2 villages in each mandal and an average of 5 farmers in each village. The survey indicated that 94% of the respondents were aware of the ill effects of Parthenium. More than 76% informed that Parthenium has been invading the area for more than last 10 years. 55% knew about the problems caused to human beings like skin allergy, asthma and fever. 17% told that children above 12 years old were affected much, and 96% of the respondents knew about the spread of Parthenium. People accepted that it grows profusely in heavy soils (45%) followed by light soils (17%). All the respondents replied that it grows profusely in the monsoon season and in soils having moisture. Further, its maximum appearance occurs in June-July, flowering in August-September and drying in October.